2017
DOI: 10.1186/s12935-017-0479-6
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of low-passage poorly-differentiated human mucoepidermoid carcinoma cells by alginate microcapsules: in vitro profiling of angiogenesis-related molecules

Abstract: BackgroundHuman mucoepidermoid carcinoma (MEC) is regarded as the most common primary salivary malignancy. High-grade MEC has a high risk of recurrence and poor prognosis. Tumor angiogenesis, induced by poorly differentiated cancer cells of high-grade MEC, contributes to tumor growth and metastasis. Therefore, elucidating molecular mechanisms underlying the pro-angiogenic ability of poorly differentiated MEC cells is critical for the understanding of high-grade MEC progression. It is well known that three-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…3D tumour models are considered to better recapitulate the in vivo tumour microenvironment compared to standard 2D cultures. In this review we have identified a total of 37 publications [ 34 , 50 , 57 , 60 , 62 , 64 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ] where 3D culture significantly altered cancer cell behaviour towards a more biomimetic response. Eighteen of these studies used 3D scaffold-based cultures and 18 studies used non scaffold-based, cell-generated extra-cellular matrix (ECM) cultures, with a single study using both approaches [ 73 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…3D tumour models are considered to better recapitulate the in vivo tumour microenvironment compared to standard 2D cultures. In this review we have identified a total of 37 publications [ 34 , 50 , 57 , 60 , 62 , 64 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ] where 3D culture significantly altered cancer cell behaviour towards a more biomimetic response. Eighteen of these studies used 3D scaffold-based cultures and 18 studies used non scaffold-based, cell-generated extra-cellular matrix (ECM) cultures, with a single study using both approaches [ 73 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Such ability to isolate specific cells further increases the capacity of studying genetic and phenotypic alterations in specific sub-sets of the cultured cells. In a recent study by Yang and co-workers [217], spherical alginate-based microcapsules were used to cultivate low passage human mucoepidermoid cells, and also to isolate angiogenesis-related molecules released from these cancer cells. The analysis of 3D cultures phenotypes and genotypes revealed a higher expression of pro-angiogenic genes and hypoxia associated factors in comparison to those obtained in standard 2D cultures [217].…”
Section: Microencapsulated 3d Modelsmentioning
confidence: 99%
“…These systems demonstrated perfusable vascular networks growing within and around the tumor spheroids [139], as well as cancer cells migrating to and infiltrating vascular networks [140]. In many cases, cancer cells were partitioned inside alginate-based microcapsules to grow in their own isolated environments [141144]. Alginate capsules are resistant to cell attachment but are also permeable to growth factors such as MCF-7 breast cancer cell-secreted VEGF and HIF1α [141].…”
Section: Biomaterials As Tools To Model Vascular Morphogenesismentioning
confidence: 99%
“…In many cases, cancer cells were partitioned inside alginate-based microcapsules to grow in their own isolated environments [141144]. Alginate capsules are resistant to cell attachment but are also permeable to growth factors such as MCF-7 breast cancer cell-secreted VEGF and HIF1α [141]. The vascularized microtumor model was further developed through the incorporation of alginate capsules containing MCF-7 cells into vascularized Collagen-I hydrogels.…”
Section: Biomaterials As Tools To Model Vascular Morphogenesismentioning
confidence: 99%